Mitochondrial transporters and disease - function and mechanism - Kunji, Edmund R.S. (Henry Stewart Talks, 2018)
Mitochondria in the human cell, Role of mitochondrial carriers in human metabolism, Sequence and structure of mitochondrial carriers, The central substrate binding site, The involvement of salt bridge networks in the transport mechanism